ANALISIS FAKTOR YANG MEMPENGARUHI KEMAMPUAN ADAPTASI FAMILY CAREGIVER DALAM MERAWAT KELUARGA DENGAN KANKER STADIUM AKHIR DI POLI ONKOLOGI RSUD DR. SOETOMO SURABAYA - Purwaningsih Purwaningsih; Elida Ulfiana; Trias Isrichawati (Universitas Airlangga, 2020)
Introduction: Caring for family members with cancer takes a long time. Various problems that arise during treatment will have an impact on the physical condition and psychological care giver so that this will have an impact on family adaptation. The purpose of this study was to analyze the factors that influence the adaptation ability of family caregivers who care for families with terminal condition cancer in the Oncology Poly RSUD Dr. Soetomo Surabaya. Methods: A cross-sectional study design. The population in this study are families who care for family members with terminal condition cancer in the Oncology Polyclinic Dr. Soetomo as many as 138 respondents were obtained by purposive sampling. The independent variables are attitude, trust, family support, coping mechanisms, and role functions while the dependent variable is the adaptability of family caregiver who care for families with terminal condition cancer. The research instrument used questionnaire attitudes, beliefs, family support, coping mechanisms, role functions and adaptability. Data analysis using Spearman Rho with significance level p ≤ 0.05. Results: Attitudes, family support, coping mechanisms, role functions are related to family caregiver's adaptability, while trust is not related to family caregiver's adaptability. Conclusion: Adaptability is needed for family caregivers in caring for families with terminal condition cancer. Future researchers are expected to intervene further to improve family support and adaptive coping mechanisms to help overcome problems that arise during the treatment of patients with cancer. Keywords: Attitude, Trust, Family Support, Coping Mechanisms, Role Function, Terminal Condition Cancer